On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

Lessons from the Arctic : how Roald Amundsen won the race to the South Pole - Kløver, Geir Olav (Fram Museum, 2017)
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Roald Amundsen : tidenes polfarer - Barr, Susan; Amundsen, Roald; Ekeberg, Jan Ove (Stenersen forl., 2005)
Keywords: Antarktis; Belgica ekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; biografier; dagbøker; oppdagelsesreiser

Belgica in the Arctic - Kjær, Kjell-G. (Polar Record, 2005)
Belgica, which Adrien de Gerlache used on the first expedition to winter in the Antarctic, was originally a bottlenose whaler named Patria, built in Norway in 1884. She was designed and constructed by Johan Chr. Jakobsen, renowned for his design of polar ships. Patria was sold to Adrien de Gerlache and renamed Belgica in 1896. In 1896–97 she was refitted and equipped in Sandefjord, Norway, for an Antarctic expedition. Nansen and Amundsen met for the first time on Belgica's deck. Late in 1899 Belgica returned to Antwerp after more than two years on an Antarctic expedition. From 1901 to 1904 Belgica returned to bottlenose whaling and, in addition, made a voyage to northeast Greenland to establish depots and build houses for the Baldwin-Ziegler Polar Expedition. In 1905 the Duc d'Orléans chartered her to survey the coast of northeast Greenland, and on her return he bought her. In 1907 and 1909 she sailed on Arctic expeditions led by the Duc d'Orléans and captained by de Gerlache. In 1916 she was sold to Det Norske Kulsyndikat and renamed Isfjord. She became a freighter carrying coal from Longyearbyen to ports in northern Norway. In 1918 she was sold and her new owner converted her into a floating cod-liver oil refinery and fish-processing plant. In 1940 she was impounded by British forces and used as a floating ammunition depot. On 19 May 1940 she was sunk during a German air raid. Her wreck was re-discovered in 1990.
Keywords: Antarktis; Belgica (skip); Belgica ekspedisjon; Roald Amundsen; overvintring; polarekspedisjoner; polarområdene

Johan Koren : feltzoolog og polar-pioner - Wikan, Steinar (Schibsted, 2000)
EN NORSK FELTZOOLOG OG POLAR-PIONER 17 år gammel drar snekkerlærlingen JOHAN KOREN ut fra hjembyen i Fredrikstad i 1897 som deltager i historiens første overvintringekspedisjon i Antarktis, Belgica-ekspedisjonen. Styrmann om bord er en landsmann, den unge Roald Amundsen. I likhet med ham, blir Koren snart kjent og omtalt som en av tidenes dristigste oppdagelsesreisende, med Antarktis og Arktis som virkefelt. Men for Koren blir berømmelsen ikke varig. Bare 39 år gammel dør han i spanskesyken, alene på et hospital i Vladivostok. Og med tiden går det slik at han blir "Gutten Norge glemte" - slik tittelen lød på en senere guttebok, inspirert av hans begivenhetsrike og dramatiske liv. Blant feltzoologer regnes han imidlertid den dag i dag som en pionerskikkelse, og rundt om i verdens zoologiske museer finnes tusenvis av vitnesbyrd om hans innsats for vitenskapen som samler av fugle- og dyrearter. Forfatteren, historikeren og biologen STEINAR WIKAN bygger denne beretningen på Johan Korens delvis bevarte dagbøker, samtlige brev, dokumenter og presseomtaler, erindringsbøker og - ikke minst - samtaler med en gammel mann i det fjerneste Sibir som kjente Koren.
Keywords: Antarktis; Belgica ekspedisjon; biografier; forskning; oppdagelser; overvintring; polarekspedisjoner; zoologi